(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The largest single factor which has caused changes, ifany, in the library and information services, is information technologyincluding computer, telecommunication, storage and other related technologies.It has made possible to introduce few new services, revolutionaries manyexisting services by providing new media, by increasing speed of processing andretrieval, by overcoming distance and communication barriers and so on.